Translation Students Representations in the Learning Process of a Foreign Language [Representaciones de Estudiantes de Traducción en el Aprendizaje de Una Lengua Extranjera] - Rubio-Manriquez, M; Singer-Contreras, N; Rubio-Martin, R (Pontificia Universidad Catolica de Chile, 2018)
This article explores language learners subjectivity in the context of a translator training programme and systematises a related didactic experience. As starting point, learners are regarded as digital natives (Prensky, 2001; Helpsper & Enyon, 2009) who consume multimodal texts (Kress, 2010; Kress & Van Leeuwen, 2001) and must develop their intercultural communicative competence (Byram, 1997; Johnson, 2004). The methodology presents a qualitative focus with two phases: i) a study on representations of which participants were 14 first-year students distributed in three groups, and ii) a systematisation of the implementation of a didactic sequence focused on the restructuring of third-year students representations. The results indicate that participants conceive foreign language mastery as systematic and discursive knowledge in real contexts of communication with native speakers, which is validated by the possibility of physical and symbolic transition to the culture where the language is spoken. Both learning and teaching are validated mostly by the proper use of productive skills. The systematization, in phase two, evidences that it is possible to incorporate students representations in the teaching and learning processes. It is concluded that students representations present contradictory elements, highlight writing as the utmost skill and point out formal aspects of language. In addition, learners identify virtual navigation and access to multimodal material as learning spaces outside the classroom which demand that they assume a protagonist role. © 2018 Pontificia Universidad Catolica de Chile. All rights reserved.